How Radical Is Embodied Creativity? Implications of 4E Approaches for Creativity Research and Teaching - Malinin, Laura H. (Frontiers in Psychology, 2019)
Modern ideas of embodiment have been influential is cognitive science for the past several decades, yet there is minimal evidence of embodied cognition approaches in creativity research or its application to educational settings. With creativity research in crisis due to conceptual, methodological, and theoretical issues, radical embodied cognitive science (RECS) may offer a framework to move the field forward. This conceptual analysis examines the current state of creativity research from the 4E (embodied, embedded, enactive, and extended) cognition and RECS perspectives. Two streams are critiqued for their potential to further knowledge about the development of creative expertise and inform educational practices. Promising directions for future research is discussed, including ways dynamical systems approaches might yield new insights about creativity skill acquisition and help address the “higher order thinking” criticisms of RECS.